Living Off Tourism. Rhetoric and Development Models in the Post-Earthquake of Central Italy (2016/2017) - Mariani, Enrico (E|C, 2022)
The earthquake that affected the central Apennines in Italy between 2016 and 2017 is considered one of the most serious socio-economic disasters in recent years. Starting from a broader field work about temporary housing, focused on the link between everyday practices and social discursiveness, this contribution explores tourism as a dense and conflicting problem field. Uncertainty about reconstruction weakens the agency and capacity of local communities to aspire, while the post-earthquake temporality of "permanent emergency" generates a kind of suspended time of dwelling. Within this framework, the paper demonstrates how the construction of temporary commercial areas is also legitimized through certain discursive strategies. If tourism is the only horizon of the post-disaster recovery, it is not only the historical condition of territorial marginality that is neutralized in the public discourse, but also every possible alternative.